DAMPAK DEFISIT ANGGARAN TERHADAP PERTUMBUHAN EKONOMI - Sawitri, Hendrin H (LPPM Universitas Terbuka, 2006)
The purpose of the research is to analyze the effect of budget deficit on economic growth. This analysis implements general evaluation estimator which is used in Didiek Susetyo researched (2001). Data economic variables used annually 1995 ? 2005. Findings shows that budget deficit have negative effect on economic growth, while the lag of ratio export income (PDB) have positive effect, that indicate export probably to increase. The attention to uphold the economic growth that some condition, accountability and transparency of government budget, fairly state-local government fiscal balance, support to increasing export and through out of crisis the Indonesia people.